Formula optimization of sustained-release ibuprofen tablet using simplex lattice design with mixture of caragenan, calsium sulphate, and PVP-K30 - Wuryanto Hadinugroho; Achmad Fudholi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Ibuprofen is one of non steroid anti inflammatory drug (NSAID), derivated propionic acid often use rheumatoid therapy. Frequented using can make unpleasant of patient, solution for this problem by sustained release ibuprofen tablet design. This experiment aim is find out the optimized formula of sustained release ibuprofen tablet with hardness of ≥ 4 kgf, brittleness of ≤ 1 %, and 0.7-0.9 mg/minutes ibuprofen rate out by using mixture of carrageenan, calcium sulphate and PVP-K30. This formula use ibuprofen as 400 mg, the mixture of carrageenan, calcium sulphate and PVP-K30 as 12 mg, so tablet total weight is 600 mg, the mixture total weight is. The proportion was optimized by using simplex lattice design special cubic model. There are seven formula in this design (each three formula consist of 100 %, three formula consists of two as 50 % : 50 % and last formula mixture three component as 33.33 % of each) to get coefficient of equation Y = a(A)+b(B)+c(C)+ab(A)(B)+ac(A)(C)+bc(B)(C)+ abc(A)(B)(C). Based of each optimized parameter equation is got contour plot and combined to superimposed contour plot, so the optimized formula can be found. Based of superimposed contour plot is mixture carrageenan:calcium sulphate:PVP-K30 comperation of optimized formula sustained release ibuprofen tablet are 0.347 : 0.233 : 0.420 to find out the optimized formula of sustained release ibuprofen tablet with the hardness as 5.71; brittleness as 0.28; and ibuprofen rate out as 0.79. The most dominant increase factor on hardness is calcium sulphate, on brittleness is carrageenan and on ibuprofen rate out is PVPK30. About interaction, the most hardness is calcium sulphate-PVP-K30, the most brittleness and ibuprofen rate out is carrageenan-calcium sulphate-PVPK30.Key words:carrageenan, calcium sulphate, PVP-K30, ibuprofen.